2008
DOI: 10.2106/jbjs.h.00485
|View full text |Cite
|
Sign up to set email alerts
|

Tribology and Wear of Metal-on-Metal Hip Prostheses: Influence of Cup Angle and Head Position

Abstract: These studies support the hypothesis that both an increased cup angle and a lateral head position increase wear in metal-on-metal hip prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 12 publications
7
106
1
Order By: Relevance
“…The steep position of the BHR cup resulted in the increase of wear rate by an order of magnitude compared with the optimal position. Similarly, in another MoM hip simulator study (28 mm head diameter), the increase of the cup inclination angle from 45° to 55° resulted in a fivefold increase of the wear rate [22]. With a 39 mm diameter MoM, the increase of the cup inclination angle from 45° to 60° resulted in a ninefold increase of the wear rate [20].…”
Section: Discussionmentioning
confidence: 84%
“…The steep position of the BHR cup resulted in the increase of wear rate by an order of magnitude compared with the optimal position. Similarly, in another MoM hip simulator study (28 mm head diameter), the increase of the cup inclination angle from 45° to 55° resulted in a fivefold increase of the wear rate [22]. With a 39 mm diameter MoM, the increase of the cup inclination angle from 45° to 60° resulted in a ninefold increase of the wear rate [20].…”
Section: Discussionmentioning
confidence: 84%
“…Elevated chromium and cobalt levels have been found in both the serum and remote organs of patients with metal-on-metal bearings [1,2,10]. Studies have also demonstrated excessive wear with onepiece metal shells in women with smaller diameter components as well as in hips in which the shell is oriented more vertically in the pelvis (a higher abduction angle) [5,11,13,16,19]. Occasionally, more dramatic local reactions to metal-on-metal articulations occur with a wide spectrum of presentations; excessive metal wear can lead to asymptomatic effusions, pseudotumors, and wide zones of soft tissue necrosis with loss of abductors and bone death [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…It appears likely hip arthroplasty based on large metal-onmetal bearings will have increased metal ion levels and higher rates of wear-related failure with higher acetabular inclination angles [20,21,31]. Previously, a few studies were directed at proper femoral component stem orientation in HRA [19,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Even though femoral neck fracture and femoral loosening were formerly reported as the most common failure modes in these studies [2,4,21], revision related to the acetabular component is being recognized more frequently in recent reports [8,11]. Previously, higher dislocation rates and increased wear rates were well-documented in standard THA with improper acetabular inclination angles [12,20,22,31]. Although large metal bearings are resistant to dislocation even with relatively high angles of inclination, several clinical studies have implicated high cup inclination angles in wear-related failures after HRA [4,13,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation